Emerging role of UFMylation in secretory cells involved in the endocrine system by maintaining ER proteostasis - Cheng, Yun; Niu, Zikang; Cai, Yafei; Zhang, Wei (Frontiers in Endocrinology, 2023)
Ubiquitin-fold modifier 1 (UFM1) is a ubiquitin-like molecule (UBL) discovered almost two decades ago, but our knowledge about the cellular and molecular mechanisms of this novel protein post-translational modification is still very fragmentary. In this review, we first summarize the core enzymes and factors involved in the UFMylation cascade, which, similar to ubiquitin, is consecutively catalyzed by UFM1-activating enzyme 5 (UBA5), UFM1-conjugating enzyme 1 (UFC1) and UFM1-specific ligase 1 (UFL1). Inspired by the substantial implications of UFM1 machinery in the secretory pathway, we next concentrate on the puzzling role of UFMylation in maintaining ER protein homeostasis, intending to illustrate the underlying mechanisms and future perspectives. At last, given a robust ER network is a hallmark of healthy endocrine secretory cells, we emphasize the function of UFM1 modification in physiology and pathology in the context of endocrine glands pancreas and female ovaries, aiming to provide precise insight into other internal glands of the endocrine system.